Odpowiedzi

2010-03-12T19:47:47+01:00
A) = -3/11 : (-28)= -3/11 * (-1/28) = 3/291

b) = -7/1 * 14/5 + 48,6 = -91/5 + 48,6 = -18,2 + 48,6 = 30,4

c) = -2 : (-2) = 1

d) -6 -20 / -5 = -26/(-5) = 5,2
Najlepsza Odpowiedź!
2010-03-12T19:56:23+01:00
A) (- 1 1/3) : (-28)=(-4/3) * (-1/28)=1/28
odwrotność liczby 1/28=28/1
b) (-7) * 1 4/5 -(-48,6)=(-7) * 9/5 -(-48,6)= -63/5 -(-48,6)= (-7) * 9/5 -(-48,6)= - 63/5 - (-48,6) = -12,6 + 48,6 = 36
c) (4-(6)) : (-2) = -2:(-2)=1
d) (12-18) - (17-(-3))= -6-(17+3) = -6-20= -26
2 1 2